Double-strand structured bioactive glass fiber and preparation method thereof
Through the electrospinning preparation and calcination treatment of double-stranded structured bioactive glass fibers, the problem of poor fiber flexibility and controllability is solved, high mechanical properties and rapid reaction ability in complex tissue environments are achieved, and bone tissue is promoted Mineralization and regeneration.
Patent Information
- Application Number
- CN202411617616.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-11-13
AI Technical Summary
The existing bioactive glass fibers have poor flexibility, poor controllability and poor mechanical adaptability, which limit their application in complex tissue environments.
Using double-strand structured bioactive glass fibers, strip bi-strand fibers are prepared by electrospinning process. The fiber surface has a continuous groove structure, including silica, calcium oxide, phosphorus pentoxide and divalent metal oxides, and calcined Treatment improves the strength and mechanical properties of the fiber.
It improves the structural flexibility and controllability of bioactive glass fibers, enhances mechanical adaptability, promotes the reaction capacity and ion release in the organism, and accelerates the tissue regeneration and repair process.
Smart Images

Figure CN119263643A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biomedical materials, and in particular to a double-strand structured bioactive glass fiber and a preparation method thereof. Background Art
[0002] Bioactive glass is widely used in the fields of bone tissue, nerve and soft tissue repair because it can form an apatite layer in the body, promote cell adhesion, proliferation and tissue regeneration. However, traditional bioactive glass materials are mostly in block or granular form with a single structure, which makes it difficult to cope with complex tissue environments. In contrast, fiber-structured bioactive glass has shown great potential in tissue repair due to its high specific surface area and excellent mechanical properties. However, most of the existing bioactive glass fibers are single-fiber structures with simple structures, poor flexibility and poor controllability, which limits their mechanical adaptability in complex tissue environments, and thus limits their application in functional applications such as biomineralization and controlled release. Summary of the invention
[0003] The problem solved by the invention is how to solve the problems of poor flexibility, poor controllability and poor mechanical adaptability of existing bioactive glass fibers.
[0004] In order to solve the above problems, the present invention provides a double-strand structured bioactive glass fiber and a preparation method thereof.
[0005] In a first aspect, the present invention provides a double-strand structured bioactive glass fiber, which is a strip-shaped double-strand fiber. The cross-section of the double-strand fiber is shaped like two intersecting circles, and the two opposite surfaces of the double-strand fiber have a groove structure extending continuously along the length direction of the double-strand fiber.
[0006] Optionally, the double-strand fiber includes a first strand of fiber and a second strand of fiber in a strip shape, and the first strand of fiber and the second strand of fiber are partially fused to form a groove structure.
[0007] Optionally, the diameters of the first fiber and the second fiber are the same, the diameters of the first fiber and the second fiber range from 200 nanometers to 10 micrometers, and the aspect ratio of the first fiber to the second fiber is between 50 and 500.
[0008] Optionally, the two-strand structured bioactive glass fibers include silicon dioxide, calcium oxide, phosphorus pentoxide, and one or more divalent metal oxides.
[0009] Optionally, the molar ratio of silicon dioxide, calcium oxide, phosphorus pentoxide and divalent metal oxide is 60-80%: 10-20%: 5-10%: 5-10%.
[0010] Optionally, the divalent metal oxide is one or more of magnesium oxide, zinc oxide, copper oxide, strontium oxide, and barium oxide.
[0011] In a second aspect, the present invention provides a method for preparing a double-strand structured bioactive glass fiber, which is used to prepare the double-strand structured bioactive glass fiber as described in any one of the above items, comprising the following steps:
[0012] S1: preparing a precursor solution: dissolving tetraethyl silicate and triethyl phosphate as precursors of SiO2 and P2O5, respectively, in deionized water, adding hydrochloric acid as a catalyst to form a uniform silica sol solution, adding one or more divalent metal salts or divalent metal salt hydrates to the silica sol solution to obtain a metal silica sol solution, adding a polymer solution to the metal silica sol solution, stirring for more than 12 hours to obtain a precursor solution, wherein the polymer solution includes a polyvinyl alcohol aqueous solution, a polyvinyl butyral aqueous solution, and a polyvinyl pyrrolidone aqueous solution;
[0013] S2: electrospinning the precursor solution at a temperature of 30±5°C to obtain precursor fibers;
[0014] S3: calcining the precursor fiber, and cooling it to room temperature to obtain a double-stranded structured bioactive glass fiber.
[0015] Optionally, the mass ratio of the metal silica sol solution to the polymer solution is 3-7:7-3.
[0016] Optionally, the concentration of the polymer solution is 5-20wt%, the molecular weight of the polyvinyl alcohol in the polymer solution is 50000-80000, the molecular weight of the polyvinyl butyral is 70000-1500000, and the molecular weight of the polyvinyl pyrrolidone is 50000-1300000.
[0017] Optionally, the calcination treatment includes two stages: preheating and drying and formal calcination. The preheating and drying is to place the precursor fiber at 60-100°C for 6-24 hours with air preheating and drying. The formal calcination temperature is set at 500-1000°C, the heating rate is 2-10°C / min, and the heating time is 2-8 hours.
[0018] The beneficial effects of the double-strand structured bioactive glass fiber and the preparation method thereof of the present invention are as follows: the two opposite surfaces of the double-strand fiber have a continuous through groove structure, which divides the double-strand fiber into two strand fiber structures, breaking through the technical barrier that the glass fiber has only a single fiber structure, and improving the structural flexibility and controllability of the bioactive glass fiber. The two strand fiber structures are entangled and cross-linked with each other, which enhances the overall strength and mechanical adaptability of the fiber, so that it exhibits better performance under both tensile and shear stresses. The design of the double-strand fiber structure can increase the surface area of the bioactive glass material, thereby improving the reactivity with body fluids in the organism, promoting the release of bioactive ions, accelerating the tissue regeneration and repair process, and being more conducive to bone tissue mineralization. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a schematic diagram of the appearance of the double-stranded structured bioactive glass fiber of Example 1 of the present invention;
[0020] Figure 2 This is a microscopic schematic diagram of a double-strand fiber of the double-strand structured bioactive glass fiber of Example 1 of the present invention;
[0021] Figure 3 for Figure 2 AA cross-section diagram;
[0022] Figure 4 is a SEM image of the double-stranded structured bioactive glass fiber of Example 1 of the present invention;
[0023] Figure 5 This is a SEM image of the double-stranded structured bioactive glass fiber of Example 1 of the present invention after being immersed in simulated body fluid and mineralized;
[0024] Figure 6 is a curve diagram of ion release results of the double-stranded structured bioactive glass fiber of Example 1 of the present invention;
[0025] Description of reference numerals:
[0026] 1. Groove structure; 2. First strand of fiber; 3. Second strand of fiber. DETAILED DESCRIPTION
[0027] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. Although certain embodiments of the present invention are shown in the accompanying drawings, it should be understood that the present invention can be implemented in various forms and should not be interpreted as being limited to the embodiments described herein. On the contrary, these embodiments are provided to provide a more thorough and complete understanding of the present invention. It should be understood that the drawings and embodiments of the present invention are only for exemplary purposes and are not intended to limit the scope of protection of the present invention.
[0028] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention;
[0029] The term "including" and its variations used in this article are open inclusions, that is, "including but not limited to"; the term "based on" is "based at least in part on"; the term "one embodiment" means "at least one embodiment"; the term "another embodiment" means "at least one other embodiment"; the term "some embodiments" means "at least some embodiments"; the term "optionally" means "optional embodiments". The relevant definitions of other terms will be given in the following description. It should be noted that the concepts of "first" and "second" mentioned in the present invention are used to distinguish different objects, rather than to describe a specific order or a primary and secondary relationship. In addition, the terms "first" and "second" are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of this application, unless otherwise specified, the meaning of "multiple" is two or more.
[0030] In response to the problems existing in the above-mentioned related technologies, the present embodiment provides a double-strand structured bioactive glass fiber and a preparation method thereof. The double-strand structured bioactive glass fiber is mainly used in biomedical fields such as bone tissue repair and regeneration, oral repair and regeneration, soft tissue repair and regeneration, vascular repair and regeneration, nerve repair and regeneration, drug delivery systems, hemostasis and antibacterial treatment, etc.
[0031] like Figure 1-4 As shown, a double-strand structured bioactive glass fiber provided by an embodiment of the present invention is a strip-shaped double-strand fiber, the cross-section of the double-strand fiber is in the shape of two intersecting circles, and the two opposite surfaces of the double-strand fiber have a continuous through groove structure 1, and the groove structure 1 extends along the length direction of the double-strand fiber.
[0032] In this embodiment, the two opposite surfaces of the double-strand fiber have a continuous groove structure 1, which divides the double-strand fiber into two fiber structures, breaking through the technical barrier that the glass fiber has only a single fiber structure, and improving the structural flexibility and controllability of the bioactive glass fiber. The two fiber structures are entangled and cross-linked with each other, which enhances the overall strength and mechanical adaptability of the fiber, making it exhibit better performance under tensile and shear stress. The design of the double-strand fiber structure can increase the surface area of the bioactive glass material, thereby improving its reactivity with body fluids in the body, promoting the release of bioactive ions, accelerating the tissue regeneration and repair process, and being more conducive to bone tissue mineralization.
[0033] It should be noted that the cross-section of the double-strand fiber in this embodiment is in the shape of two intersecting circles, which does not mean that the two circles are strictly the intersection of two arc contours at the intersection. In fact, the two circles present a smooth rounded shape at the intersection.
[0034] Optionally, the double-strand fiber includes a first strand of fiber 2 and a second strand of fiber 3 in a strip shape, and the first strand of fiber 2 and the second strand of fiber 3 are partially fused to form a groove structure 1 .
[0035] In this optional embodiment, the first fiber strand 2 and the second fiber strand 2 are fused, so that the first fiber strand 2 and the second fiber strand 3 are entangled and cross-linked with each other, thereby enhancing the overall strength and mechanical adaptability of the fibers.
[0036] Optionally, the diameters of the first fiber 2 and the second fiber 3 are the same, the diameters of the first fiber 2 and the second fiber 3 range from 200 nanometers to 10 micrometers, and the aspect ratio of the first fiber 2 to the second fiber 3 is between 50 and 500.
[0037] Specifically, the aspect ratio refers to the ratio of the length to the diameter of the fiber. In this optional embodiment, the double-stranded structured bioactive glass fiber is a micro / nano-scale fiber that can reach the surface of biological tissues and thus play a role in repairing biological tissues.
[0038] Optionally, the two-strand structured bioactive glass fibers include silicon dioxide, calcium oxide, phosphorus pentoxide, and one or more divalent metal oxides.
[0039] Specifically, the divalent metal oxide includes, but is not limited to, one or more of magnesium oxide (MgO), zinc oxide (ZnO), copper oxide (CuO), strontium oxide (SrO), and barium oxide (BaO).
[0040] Optionally, the molar ratio of silicon dioxide, calcium oxide, phosphorus pentoxide and divalent metal oxide is 60-80%: 10-20%: 5-10%: 5-10%.
[0041] In this optional embodiment, silicon dioxide, calcium oxide and phosphorus pentoxide constitute a silica sol solution, which is an essential component of glass fiber.
[0042] In a second aspect, the present invention provides a method for preparing a double-strand structured bioactive glass fiber, which is used to prepare the double-strand structured bioactive glass fiber as described in any one of the above items, comprising the following steps:
[0043] S1: preparing a precursor solution: dissolving tetraethyl silicate and triethyl phosphate as precursors of SiO2 and P2O5, respectively, in deionized water, adding hydrochloric acid as a catalyst to form a uniform silica sol solution, adding one or more divalent metal salts or divalent metal salt hydrates to the silica sol solution to obtain a metal silica sol solution, adding a polymer solution to the metal silica sol solution, stirring for more than 12 hours to obtain a precursor solution, wherein the polymer solution includes a polyvinyl alcohol aqueous solution, a polyvinyl butyral aqueous solution, and a polyvinyl pyrrolidone aqueous solution;
[0044] S2: electrospinning the precursor solution at a temperature of 30±5°C to obtain precursor fibers;
[0045] S3: calcining the precursor fiber, and cooling it to room temperature to obtain a double-stranded structured bioactive glass fiber.
[0046] In this embodiment, a polyvinyl alcohol aqueous solution, a polyvinyl butyral aqueous solution and a polyvinyl pyrrolidone aqueous solution are added to a silica sol solution to form a precursor solution, the ambient temperature of the electrospinning equipment is adjusted to 30±5°C, and the precursor solution is electrospun. Under the action of the high-voltage electric field of electrospinning, relying on the rapid volatilization and phase separation of the solvent vinyl alcohol and water in the electrospinning process, the precursor solution is stretched to form double-strand structured micro / nano fibers, and the fibers are collected on a receiving drum and calcined to obtain double-strand structured bioactive glass fibers.
[0047] Specifically, tetraethyl silicate and triethyl phosphate are used as precursors of SiO2 and P2O5, respectively, and dissolved in deionized water. Subsequently, hydrochloric acid is added as a catalyst to promote hydrolysis and form a uniform silica sol solution.
[0048] Specifically, for the electrospinning operation of the precursor solution, it is first necessary to adjust the ambient temperature and humidity of the electrospinning equipment; next, place the precursor solution in a syringe with a metal needle; then, adjust the distance between the metal needle and the receiver, set the positive and negative high-voltage power supplies, and control the injection speed of the solution and the rotation speed of the receiving roller; finally, under the action of the high-voltage electric field, stretch the precursor solution to form double-strand structured micro / nano fibers, and collect them on the receiving roller.
[0049] The operating parameters and environmental parameters for electrospinning the precursor solution include but are not limited to: the electrospinning equipment used, mainly including positive and negative high-voltage power supplies, solution injection devices, roller receiving devices, and environmental temperature and humidity adjustment devices. The specific operation of the electrospinning step of the precursor solution includes the following parameters:
[0050] a) adjusting the ambient temperature and humidity of the electrospinning equipment, wherein the ambient temperature is 30±5 degrees Celsius and the relative humidity is 40±10%;
[0051] b) placing the precursor solution in a syringe with a metal needle, wherein the diameter of the metal needle is 0.5 mm to 1.5 mm and the specification of the syringe is 5 ml to 20 ml;
[0052] c) adjusting the spinning distance between the metal needle and the receiver: 5 cm to 30 cm; setting positive and negative high voltage power supplies, wherein the positive high voltage source voltage is: 10 kV to 40 kV, and the negative high voltage source voltage is: 2 kV to 10 kV;
[0053] d) Control the injection speed of the solution: 0.01 mm / min to 0.05 mm / min; the rotation speed of the receiving roller: 20 rpm to 200 rpm.
[0054] Optionally, the mass ratio of the metal silica sol solution to the polymer solution is 3-7:7-3.
[0055] In this embodiment, at this mass ratio, the rapid volatilization of the vinyl alcohol and water in the precursor solution during the electrospinning process and the phase separation effect cause the fibers to form a double-strand structure.
[0056] Therefore, when preparing the precursor solution, the ratio of the silica sol solution to the polymer solution is adjusted; and when performing electrospinning, the variable of the ambient temperature is adjusted. These two parameters are combined to achieve the rapid volatilization and phase separation of vinyl alcohol and water, and finally obtain a double-stranded structured bioactive glass fiber material.
[0057] Optionally, the concentration of the polymer solution is 5-20wt%, the molecular weight of the polyvinyl alcohol in the polymer solution is 50000-80000, the molecular weight of the polyvinyl butyral is 70000-1500000, and the molecular weight of the polyvinyl pyrrolidone is 50000-1300000.
[0058] Optionally, the calcination treatment includes two stages: preheating and drying and formal calcination. The preheating and drying is to place the precursor fiber at 60-100°C for 6-24 hours with air preheating and drying. The formal calcination temperature is set at 500-1000°C, the heating rate is 2-10°C / min, and the heating time is 2-8 hours.
[0059] In this optional embodiment, preheating and drying can ensure that the residual solvent in the precursor fiber is completely removed.
[0060] Specifically, during the formal calcination, the precursor fiber felt is placed in a tubular furnace or a muffle furnace, and after the calcination is completed, it is naturally cooled to room temperature.
[0061] The present invention is further described below in conjunction with specific embodiments.
[0062] Example 1: Preparation of double-stranded structured bioactive glass fibers.
[0063] 1. 6 g of tetraethyl orthosilicate, 2.25 g of triethyl phosphate, 0.075 g of phosphoric acid, and 7.5 g of deionized water were uniformly mixed to prepare a silica sol solution; 10 g of polyvinyl alcohol was dissolved in 90 g of deionized water solution and heated to prepare a polymer solution; 1.75 g of calcium nitrate tetrahydrate, 0.25 g of strontium nitrate, and 17.83 g of polyvinyl alcohol solution were added to the above silica sol solution to prepare a precursor solution;
[0064] 2. Place the precursor solution in a 5mL syringe with a 1mm diameter metal needle, use an electrospinning device for spinning, and receive the precursor fiber through a roller receiver. The electrospinning process parameters are: positive voltage 15 kV, negative voltage 2 kV, spinning distance 15 cm; solution injection speed 0.03 mm / min, roller receiving speed 100 rpm, ambient temperature: 30°C, ambient relative humidity: 40%.
[0065] 3. The precursor fiber was placed in a blast drying oven and dried at 60°C for 8 hours. It was then placed in a tube furnace and calcined at 800°C at 5°C / min in an air atmosphere for 2 hours to remove the polyvinyl alcohol component and obtain a double-stranded structured bioactive glass fiber. Figure 1 , the schematic diagram of the microscopic double-strand fiber structure is shown in Figure 2 and Figure 3 , microscopic morphology Figure 4 SEM image of .
[0066] Example 2: Preparation of double-stranded structured bioactive glass fibers.
[0067] 1. Evenly mix 5.5g of tetraethyl orthosilicate, 2.25g of triethyl phosphate, 0.075g of phosphoric acid, and 7.5g of deionized water to prepare a silica sol solution; dissolve 10g of polyvinyl alcohol in 90g of deionized water and heat to prepare a polymer solution; add 1.75g of calcium nitrate tetrahydrate, 0.25g of magnesium nitrate, and 25.98g of polyvinyl alcohol solution to the above silica sol solution to prepare a precursor solution;
[0068] 2. Place the precursor solution in a 10mL syringe with a 0.5mm diameter metal needle, use an electrospinning device for spinning, and receive the precursor fiber through a roller receiver. The electrospinning process parameters are: positive voltage 25 kV, negative voltage 5 kV, spinning distance 5 cm; solution injection speed 0.01 mm / min, roller receiving speed 20 rpm, ambient temperature: 25°C, ambient relative humidity: 30%.
[0069] 3. The precursor fiber was placed in a forced air drying oven and dried at 80°C for 6 hours. It was then placed in a tubular furnace and heated to 500°C at 2°C / min in an air atmosphere for 8 hours to remove the polyvinyl alcohol component and obtain a double-stranded structured bioactive glass fiber.
[0070] Example 3: Preparation of double-stranded structured bioactive glass fibers.
[0071] 1. 6 g of tetraethyl orthosilicate, 2.25 g of triethyl phosphate, 0.075 g of phosphoric acid, and 7.5 g of deionized water were uniformly mixed to prepare a silica sol solution; 5 g of polyvinyl butyral was dissolved in 95 g of deionized water solution and heated to prepare a polymer solution; 1.75 g of calcium nitrate tetrahydrate, 0.8 g of magnesium nitrate hexahydrate, 0.125 g of strontium nitrate, and 12.33 g of polyvinyl butyral solution were added to the above silica sol solution to prepare a precursor solution;
[0072] 2. Place the precursor solution in a 20mL syringe with a 1.5mm diameter metal needle, use an electrospinning device for spinning, and receive the precursor fiber through a roller receiver. The electrospinning process parameters are: positive voltage 40 kV, negative voltage 10 kV, spinning distance 30 cm; solution injection speed 0.05 mm / min, roller receiving speed 200 rpm, ambient temperature: 35°C, ambient relative humidity: 50%.
[0073] 3. The precursor fiber was placed in a forced air drying oven and dried at 100°C for 8 hours. It was then placed in a tube furnace and heated to 1000°C in an air atmosphere at 10°C / min for 2 hours to remove the polyvinyl alcohol component and obtain a double-stranded structured bioactive glass fiber.
[0074] Effect Example
[0075] The double-stranded structured bioactive glass fiber prepared in Example 1 was immersed in 10 ml of human body simulation liquid and placed on a constant temperature shaker at 37 degrees for 3 days. The sample was taken out and washed with deionized water. As a result, carbonate hydroxyapatite was formed on the surface of the product. The SEM image after mineralization is shown in FIG. Figure 5 Carbonated hydroxyapatite promotes cell adhesion, proliferation and tissue regeneration, and is widely used in the fields of bone tissue, nerve and soft tissue repair.
[0076] The double-stranded structured bioactive glass fiber prepared in Example 1 was immersed in 10 ml of ultrapure water and placed on a constant temperature shaker at 37 degrees for 1, 3, 7, 14, 21, and 28 days, respectively. Samples were taken out regularly and the Si, Ca, P, and Sr ion concentrations in the ultrapure water were collected by inductively coupled plasma emission spectroscopy. The results are shown in FIG. Figure 6 .
[0077] Depend on Figure 6 It can be seen that with the increase of the placement days, the concentrations of Si, Ca, P and Sr ions gradually increased. It can be seen that the double-stranded structured bioactive glass fiber has a strong ability to release bioactive ions, accelerates the tissue regeneration and repair process, is more conducive to bone tissue mineralization, and shows great potential in tissue repair.
[0078] Although the present invention is disclosed as above, the protection scope of the present invention is not limited thereto. Those skilled in the art may make various changes and modifications without departing from the spirit and scope of the present invention, and these changes and modifications will fall within the protection scope of the present invention.
Claims
1. A double-stranded structured bioactive glass fiber, characterized in that: The double-strand fiber is in the shape of a strip, the cross section of which is in the shape of two intersecting circles, and the two opposite surfaces of the double-strand fiber both have a groove structure extending continuously along the length direction of the double-strand fiber.
2. The double-stranded structured bioactive glass fiber according to claim 1, characterized in that: The double-strand fiber includes a first strand of fiber and a second strand of fiber in a strip shape, and the first strand of fiber and the second strand of fiber are partially fused to form the groove structure.
3. The double-stranded structured bioactive glass fiber according to claim 2, characterized in that: The diameters of the first fiber and the second fiber are the same, the diameters of the first fiber and the second fiber range from 200 nanometers to 10 micrometers, and the aspect ratio of the first fiber and the second fiber is between 50 and 500.
4. The double-stranded structured bioactive glass fiber according to claim 1, characterized in that: The two-strand structured bioactive glass fiber includes silicon dioxide, calcium oxide, phosphorus pentoxide and one or more divalent metal oxides.
5. The double-stranded structured bioactive glass fiber according to claim 4, characterized in that: The molar ratio of silicon dioxide, calcium oxide, phosphorus pentoxide and divalent metal oxide is 60-80%: 10-20%: 5-10%: 5-10%.
6. The double-stranded structured bioactive glass fiber according to claim 4, characterized in that: The divalent metal oxide is one or more of magnesium oxide, zinc oxide, copper oxide, strontium oxide and barium oxide.
7. A method for preparing a double-strand structured bioactive glass fiber, characterized in that: The method for preparing the double-strand structured bioactive glass fiber according to any one of claims 1 to 6 comprises the following steps: S1: preparing a precursor solution: dissolving tetraethyl silicate and triethyl phosphate as precursors of SiO2 and P2O5, respectively, in deionized water, adding hydrochloric acid as a catalyst to form a uniform silica sol solution, adding one or more divalent metal salts or divalent metal salt hydrates to the silica sol solution to obtain a metal silica sol solution, adding a polymer solution to the metal silica sol solution, stirring for more than 12 hours to obtain a precursor solution, wherein the polymer solution includes a polyvinyl alcohol aqueous solution, a polyvinyl butyral aqueous solution and a polyvinyl pyrrolidone aqueous solution; S2: electrospinning the precursor solution at a temperature of 30±5° C. to obtain precursor fibers; S3: calcining the precursor fiber, and cooling it to room temperature after calcination to obtain a double-strand structured bioactive glass fiber.
8. The method for preparing a double-strand structured bioactive glass fiber according to claim 7, characterized in that: The mass ratio of the metal silica sol solution to the polymer solution is 3-7:7-3.
9. The method for preparing a double-strand structured bioactive glass fiber according to claim 7, characterized in that: The concentration of the polymer solution is 5-20wt%, the molecular weight of the polyvinyl alcohol in the polymer solution is 50000-80000, the molecular weight of the polyvinyl butyral is 70000-1500000, and the molecular weight of the polyvinyl pyrrolidone is 50000-1300000.
10. The method for preparing a double-strand structured bioactive glass fiber according to claim 7, characterized in that: The calcination treatment includes two stages: preheating and drying and formal calcination. The preheating and drying is to place the precursor fiber at 60-100°C for 6-24 hours by air preheating and drying. The calcination temperature of the formal calcination is set at 500-1000°C, the heating rate is 2-10°C / min, and the heating time is 2-8 hours.
Citation Information
Patent Citations
Preparation method of ultrathin, super-elastic, sweat-removing and warm keeping pajamas underwear fabric
CN112111842A
Guided tissue regeneration membrane as well as preparation method and application thereof
CN113117150A
Flexible inorganic nanofiber composite scaffold and preparation method thereof
CN114588317A
Spinner for mfg. dual-component fibers
CN1147238A
Antibiotic perspire synthetic fiber
CN204982162U